Pengaruh CEO Duality, Financial Distress, Audit Delay Dan Ukuran Perusahaan Terhadap Ketepatwaktuan (Timeliness) Pelaporan Keuangan (Studi Empiris Pada Perusahaan Sektor Property & Real Estate Yang Terdaftar Di BEI Periode 2017-2019) - Fitri Yani (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
Timeliness of financial reporting is an important thing that needs to be considered. Given the high interest of companies to go public in Indonesia, which indirectly affects the increase in companies that are subject to securities trading suspensions as sanctions for companies that are late in submitting their financial reports. This study aims to examine the effect of CEO duality, financial distress, audit delay and firm size on the timeliness of financial reporting of property & real estate sector companies listed on the Indonesia Stock Exchange. The population used is all property & real estate sector companies listed on the IDX in 2017-2019. The sample was determined using purposive sampling method in order to obtain a sample of 40 companies. Data analysis was carried out by logistic regression analysis using the SPSS 17 program. The results of the hypothesis test of this study indicate that the CEO duality variable and the audit delay variable affect the timeliness of financial reporting. Meanwhile, the financial distress variable and the firm size variable have no effect on the timeliness of financial reporting. The limitation of this research is that the sample in the study cannot explain the timeliness of financial reporting for all companies listed on the IDX because they only come from property & real estate sector companies. In addition, the difficulty of obtaining information related to the CEO duality variable clearly and the use of dummy measurements to measure the timeliness of financial reporting causes the data of this study to be less varied.